2007
DOI: 10.1109/led.2007.894654
|View full text |Cite
|
Sign up to set email alerts
|

Charge Trapping and TDDB Characteristics of Ultrathin MOCVD $\hbox{HfO}_{2}$ Gate Dielectric on Nitrided Germanium

Abstract: In this letter, we investigate the long-term reliability characteristics of ultrathin HfO 2 dielectrics on nitrided germanium for the first time. Stress-polarity dependence in charge trapping and time-dependent dielectric-breakdown (TDDB) characteristics has been observed in germanium n-and p-type devices. The p-MOS devices exhibit severe charge trapping under stress, while no significant charge trapping and stress-induced leakage current were found in the n-MOS devices. In terms of operationvoltage projection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Many approaches were investigated to form a stable and desirable IL with Ge surface nitridation. One of the most frequently used methods was thermal NH 3 treatment at various temperatures [12,[29][30][31][32][33][34][35][36]. Single GeO x N y [29,32] or Ge 3 N 4 [37] layers were attempted as gate dielectrics.…”
Section: Nitride Passivation Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches were investigated to form a stable and desirable IL with Ge surface nitridation. One of the most frequently used methods was thermal NH 3 treatment at various temperatures [12,[29][30][31][32][33][34][35][36]. Single GeO x N y [29,32] or Ge 3 N 4 [37] layers were attempted as gate dielectrics.…”
Section: Nitride Passivation Layermentioning
confidence: 99%
“…Single GeO x N y [29,32] or Ge 3 N 4 [37] layers were attempted as gate dielectrics. However, since they possess a rather low k value, more reports were using GeO x N y [30,31,[33][34][35] or GeN x [38,39] as a passivation layer, with another higher k dielectric on top. Otani et al reported a low D it of 4 × 10 11 eV −1 cm −2 at midgap using a 2 nm thick GeN x passivation layer [38], while a lower D it of 1.8 × 10 11 eV −1 cm −2 was demonstrated with a slightly thicker (∼2.4 nm) GeN x IL [39].…”
Section: Nitride Passivation Layermentioning
confidence: 99%
“…The nitridation of Ge surfaces prior to high-k film deposition is one of the best-known solutions because it is effective in suppressing Ge diffusion in metal oxides and leads to improved performance of Ge-based devices. [4][5][6][7][8][9][10][11] Annealing in NH 3 ambient is widely used for Ge surface nitridation and the formation of the GeON interface layer. [6][7][8][9][10] However, these methods for introducing the nitrogen element always involve high-temperature treatment above 550 °C.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Annealing in NH 3 ambient is widely used for Ge surface nitridation and the formation of the GeON interface layer. [6][7][8][9][10] However, these methods for introducing the nitrogen element always involve high-temperature treatment above 550 °C. Since a clean Ge surface without any incorporation of oxygen is totally inert to NH 3 at temperatures up to 600 °C, 12) high-temperature treatment would result in nitrogen accumulation at the Ge/GeON interface, resulting in deterioration of the interface properties.…”
Section: Introductionmentioning
confidence: 99%